Caffeine Use in Long-Distance Running: Timing, Dosage, and Multi-Dimensional Effects on Performance and Perceived Effort. A Review - Duda, Joanna; Kędzia, Jakub; Racisz, Kinga; Obcowska, Alicja; Racisz, Paweł; Walendzik, Aleksandra (Quality in Sport, 2025)
Introduction and aim of the study: Caffeine is one of the most widely used ergogenic aids in endurance sports due to its potential to enhance both physical and cognitive performance. Among long-distance runners, its effectiveness depends on dosage, timing of intake, and individual response. This review aims to summarize current evidence on the effects of caffeine dosage and timing in long-distance running. Materials and Methods: A literature review was conducted based on studies published between 2013 and 2024 in PubMed and Google Scholar. Keywords included: “caffeine,” “running,” “endurance,” “performance,” “timing,” “dosage,” “supplementation,” and “perceived exertion.” Included studies focused on recreational and trained long-distance runners, emphasizing randomized controlled trials and systematic reviews. Results: Findings suggest that moderate caffeine intake (3–6 mg/kg), consumed 45–60 minutes prior to exercise, enhances endurance performance and lowers perceived exertion. Key mechanisms include stimulation of the central nervous system, increased alertness, improved motor unit recruitment, delayed fatigue, and enhanced post-exercise blood flow. However, individual variability, habitual caffeine use, and potential side effects—such as gastrointestinal discomfort or sleep disruption—affect outcomes. Conclusion: Strategically used, caffeine can boost performance and reduce effort perception in long-distance runners. Optimal effects are achieved through personalized dosage and timing, ideally refined during training. Future research should explore long-term use, sex-specific responses, and application in diverse race settings.